Designing for Maintainability, Failure Resilience, and Evolvability in Ubiquitous Computing Software - Ponnekanti, Shankar; Johanson, Brad; Kiciman, Emre; Fox, Armando (2002)
The design constraints in ubiquitous computing (ubicomp) differ from those traditionally emphasized by the systems community: evolvability, long-term maintainability, and robustness to transient failures are essential, while scalability and performance are lesser concerns, due to the nature of ubicomp itself and the performance of today's commodity equipment. We show how these observations are reflected in the design of iROS, a ubicomp software framework in production use. In particular, we show that a centralized architecture directly enables the ubicomp programming abstractions needed while providing the best solution for evolvability and maintainability/deployability, and that we can achieve the required robustness through a fast-recovery strategy, which allows a simple centralized implementation of the architecture. Throughout, we achieve performance, scalability, and recovery behavior sufficient for typical operation.
PG 2006